Transfer Hydrogenations of Alkenes with Formate on Pd/C: Synthesis of Dihydrocinchona Alkaloids - Wu, Haotian; Hintermann, Lukas (Synthesis, 2013)
Protocols for preparative (1–80 gram scale) transfer hydrogenations of alkenes over a palladium on carbon catalyst using formic acid/ammonium formate as hydrogen donor are presented. Cinchona alkaloids have been converted to their dihydro derivatives in >94% yield.
Keywords: alkaloids; alkenes; catalysis; hydrogen transfer; hydrogenation; palladium